2017
DOI: 10.1093/qjmed/hcw223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of anisocytosis measured as a red cell distribution width in patients with colorectal cancer

Abstract: : RDW is an integrative parameter reflecting tumor specific features and shows significant association with overall survival in patients with CRC. This is especially important in patients with stage 2 disease where elevation in preoperative RDW values can contribute to recognition of higher risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…RDW was also found to be higher in more advanced T stages, N stages and in the presents of metastases. Similarly, Kust et al 24 , www.nature.com/scientificreports www.nature.com/scientificreports/ in a retrospective study of 90 patients with CRC, found that H-RDW was associated to a poorer overall survival. However, H-RDW was a negative prognostic factor only in stage II cancers.…”
Section: Discussionmentioning
confidence: 82%
“…RDW was also found to be higher in more advanced T stages, N stages and in the presents of metastases. Similarly, Kust et al 24 , www.nature.com/scientificreports www.nature.com/scientificreports/ in a retrospective study of 90 patients with CRC, found that H-RDW was associated to a poorer overall survival. However, H-RDW was a negative prognostic factor only in stage II cancers.…”
Section: Discussionmentioning
confidence: 82%
“…This is consistent with findings in other studies, elevated RDW levels have been shown to be an independent marker for mortality after colorectal cancer surgery, coronary bypass surgery and in elderly patients who underwent fixation of hip fracture. [ 17 20 , 51 ] While we do not have data in our study on the cause of mortality, elevated RDW have been associated with an increased risk of cardiovascular events and all-cause mortality in patients with and without cardiovascular disease[ 14 , 16 , 41 , 52 ]. Elevated RDW is also associated with stroke occurrence[ 53 ] and increased all-cause mortality in patients admitted to intensive care[ 54 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…High preoperative RDW levels is associated with reduced survival after colorectal cancer surgery, in children undergoing surgical repair of congenital heart disease, and in elderly patients who underwent fixation of hip fracture. [ 17 20 ] It has been postulated that higher RDW levels reflects abnormal bone marrow activity, which may be due to chronic malnutrition, inflammation or high levels of circulating reactive oxygen species. [ 21 25 ] High RDW levels are found in a heterogeneous group of conditions, which can be further categorized by the MCV levels [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RDW is a measure of variability of red blood cell volume, that is routinely examined with the complete blood count and it represents quantitative measure of anisocytosis. An elevated RDW in peripheral blood may be associated with different types of anemias, as well as certain liver disorders and systemic inflammation [ 14 ]. Additionally, elevated RDW has also been reported as a predictor of adverse outcomes in patients with myocardial infarction, venous thromboembolism, ischemic stroke and cerebral infarction over a past few years [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated RDW in peripheral blood may be associated with different types of anemias, as well as certain liver disorders and systemic inflammation [ 14 ]. Additionally, elevated RDW has also been reported as a predictor of adverse outcomes in patients with myocardial infarction, venous thromboembolism, ischemic stroke and cerebral infarction over a past few years [ 14 17 ]. However, recent studies showed that RDW increased in patients with malignant tumors.…”
Section: Discussionmentioning
confidence: 99%